2011
DOI: 10.3892/ol.2011.265
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18-labeled boronophenylalanine positron emission tomography for oral cancers: Qualitative and quantitative analyses of malignant tumors and normal structures in oral and maxillofacial regions

Abstract: Abstract. The present study aimed to demonstrate the features of fluorine-18-labeled boronophenylalanine positron emission tomography ( 18 F-BPA-PET) to reveal oral cancer, as well as normal structures in the oral and maxillofacial regions. We analyzed 18 F-BPA-PET findings from 8 patients with histologically confirmed recurrent and/or advanced oral cancer scheduled for boron neutron capture therapy. The capacity of 18 F-BPA-PET to delineate tumor and normal structures was assessed qualitatively and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Two different tumor types were examined in our study. Our 18 F–BPA findings for SCC were consistent with previous studies [ 28 , 31 ]. However, the characteristics of dynamic 18 F–BPA accumulation in radioresistant head and neck carcinomas, such as mucoepidermoid carcinomas and adenoid cystic carcinomas, is unknown [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Two different tumor types were examined in our study. Our 18 F–BPA findings for SCC were consistent with previous studies [ 28 , 31 ]. However, the characteristics of dynamic 18 F–BPA accumulation in radioresistant head and neck carcinomas, such as mucoepidermoid carcinomas and adenoid cystic carcinomas, is unknown [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…From these results and the stability of l -[ 18 F]FBPA described later, eluent 10 was selected for routine clinical use because of the small amount of one additive in physiological saline and ease of eluent preparation. The clinical injection volumes of l -[ 18 F]FBPA separated with eluent 10 (1120 MBq/13.2 ml, Table 2 ), were expected to be 2.6–3.9 ml/60 kg when the radioactive injection doses in l -[ 18 F]FBPA PET were 3.7–5.55 MBq/kg [ 38 , 39 ], and one l -[ 18 F]FBPA preparation can be used for 2 subjects with one PET scanner or 3–4 subjects with two PET scanners. In four l -[ 18 F]FBPA preparations separated with eluent 10 and collected through a 0.22 µm membrane filter, sterility and apyrogenicity (< 0.0029 EU/ml) of the l -[ 18 F]FBPA injection and filter integrity (≥ 330 kPa) were confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…This type of quantitative evaluation has not been tried in other malignant tumors; however, Morita et al recently reported that the T / N ratios of 18 F-FBPA in head and neck cancers and malignant melanoma were not significantly changed over 120 min in spite of a slight decrease in 18 F-FBPA uptake [ 85 ]. In evaluating the T / N ratio of 18 F-FBPA in patients with head and neck cancers, it is notable that the uptake of 18 F-FBPA was higher in the dorsum tongue, submandibular gland, parotid gland, and tongue in this order among normal tissues in the oral and maxillofacial regions than in normal brain [ 86 ]. The averaged ratios ( n = 8) of T / B and tumor-to-dorsum tongue were 3.25 (range 2.34–5.40) and 1.25 (range 0.95–2.10), respectively.…”
Section: Clinical Studiesmentioning
confidence: 99%